2018
DOI: 10.1080/0144929x.2018.1424937
|View full text |Cite
|
Sign up to set email alerts
|

Flow on the Internet: a longitudinal study of Internet addiction symptoms during adolescence

Abstract: Internet Addiction (IA) constitutes an excessive internet use behavior with significant impact on the user's wellbeing. Online flow describes the users' level of being absorbed by their online activity. The present study investigated age-related, gender, and flow effects on IA in adolescence. The sample comprised 648 adolescents who were assessed twice at age 16 and 18 years. IA was assessed using the Internet Addiction Test and online flow was assessed using the Online Flow Questionnaire. A three-level hierar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 70 publications
8
81
0
1
Order By: Relevance
“…In this context, gamers experiencing symptoms of depression, who might be more vertically individualistically orientated may find themselves at a significantly greater risk of developing symptoms of DG. This finding supports a significant body of literature advocating the influence of cultural orientation on the associations between psychopathologies and addictive behaviors in general, and in particular DG (Singelis et al, 1995;Györkös et al, 2013;Winkler et al, 2013;Taymur et al, 2016;Stavropoulos, Anderson et al, 2017;Stavropoulos et al, 2018c). More specifically, employing the integrative internet abuse framework, suggested by Stavropoulos et al (2016), a more vertically individualistic orientation may foster and host achievement, competition, and ranking drives that when matched by mechanisms of the game could render the gamer more vulnerable to DG (Singelis et al, 1995;Györkös et al, 2013;Stavropoulos et al, 2018b).…”
Section: The Significance Of Culture In the Depression-disordered Gamsupporting
confidence: 80%
See 1 more Smart Citation
“…In this context, gamers experiencing symptoms of depression, who might be more vertically individualistically orientated may find themselves at a significantly greater risk of developing symptoms of DG. This finding supports a significant body of literature advocating the influence of cultural orientation on the associations between psychopathologies and addictive behaviors in general, and in particular DG (Singelis et al, 1995;Györkös et al, 2013;Winkler et al, 2013;Taymur et al, 2016;Stavropoulos, Anderson et al, 2017;Stavropoulos et al, 2018c). More specifically, employing the integrative internet abuse framework, suggested by Stavropoulos et al (2016), a more vertically individualistic orientation may foster and host achievement, competition, and ranking drives that when matched by mechanisms of the game could render the gamer more vulnerable to DG (Singelis et al, 1995;Györkös et al, 2013;Stavropoulos et al, 2018b).…”
Section: The Significance Of Culture In the Depression-disordered Gamsupporting
confidence: 80%
“…Conversely, research has suggested that excessive internet gaming behavior places gamers at higher risk for real-life dysfunction (e.g., the loss of one's job) that would in turn precipitate and/or perpetuate symptoms of depression (Griffiths, Kuss & Pontes, 2016;Adams et al, 2018;Stavropoulos et al, 2018c). These interactions advocate bi-directional and cyclical associations, whereby symptoms of depression and DG can not only initiate and maintain one another but may also occur concurrently to exacerbate one another's severity (Stavropoulos, Kuss, Griffiths & Motti-Stefanidi, 2016;Liu et al, 2018).…”
Section: Depression and Disordered Gaming Bondmentioning
confidence: 99%
“…The far-reaching implications of social media compulsive use has r increasingly attratcted attention from various researchers and scholars (LaRose et al, 2011;Meerkerk, Eijnden, & Garretsen, 2006;Meerkerk, Van Den Eijnden, Vermulst, & Garretsen, 2009;Wallace, 2014, Kumar, Kumar, & Bhasker, 2018. Further, as past research has cited more negative impacts of both technology and social media use on specific populations (Stavropoulos et al, 2018), social media compulsive use research has increasingly focused on students (Bernoff & Schadler, 2010;Dahlstrom, 2012;Jacobsen & Forste, 2011;LaRose, et al, 2011). For example, in their research of social media use by students, LaRose, et al (2011) concluded that compulsive use of web applications has negative academic, personal, and professional consequences, with compulsive use potentially resulting in diminished self-regulation, loss of self-control, and increased dysphoria.…”
Section: Social Media Compulsive Use Impactsmentioning
confidence: 99%
“…Further, past research (e.g. Stavropoulos et al, 2018) has reported varied negative outcomes of social media compulsive use, particularly for those that are unable to limit the amount of time in which they interact with social media applications. Compulsive use can be identified through behaviours such as restlessness, preoccupation with social media, moodiness, and depression, and can negatively impact personal, professional, and educational interactions, relationships, and performance (Mazer & Ledbetter, 2012).…”
Section: Research Modelmentioning
confidence: 99%
See 1 more Smart Citation